Impact of the diagnosis and treatment of cancer on the course of inflammatory bowel disease. (1st August 2014) - Rajca, S.; Seksik, P.; Bourrier, A.; Sokol, H.; Nion-Larmurier, I.; Beaugerie, L.; Cosnes, J.
Abstract: Background: The effects of extra-intestinal cancer on the course of inflammatory bowel disease (IBD) are poorly understood. Aim: To evaluate the impact of cancer and its management on IBD outcomes. Methods: A total 80 IBD patients (51 Crohn's disease, 29 ulcerative colitis; 33 men, median age at cancer diagnosis 48 yrs) diagnosed with extra-intestinal cancer were selected from a prospective database. IBD activity and therapeutic requirements (assessed year-by-year) were compared before and after cancer diagnosis, with a control group of patients without cancer matched for gender, birth date, date of IBD diagnosis and IBD phenotype. Results: Paired comparisons of the consecutive periods before and after cancer diagnosis did not show significant changes in median (IQR) percentages of years with active disease (27% [0–50] vs. 19% [0–53]), while the proportion of patient-years on any immunosuppressant remained stable (26% vs. 28%). Chemotherapy had no significant effect on IBD activity. Compared to controls, patients with cancer had a similar IBD activity and use of anti-TNF, but less use of immunomodulators (19% vs. 25%, p < 0, 001) and an increased rate of surgery (4% vs. 2.5%, p < 0, 05). Individual variations in IBD activity after cancer diagnosis were not significantly different in patients with cancer and their matched controls. Conclusion: Occurrence of extra-intestinal cancer impacts IBD therapeutic management, with a trend towards less use of immunomodulators and more surgery. In the long-term, cancer diagnoses and treatments do not modify IBD outcomes.